Low-velocity impact on high-strength steel sheets: An experimental and numerical study. (February 2016) - Gruben, G.; Langseth, M.; Fagerholt, E.; Hopperstad, O.S.
Highlights: Low-velocity and quasi-static punch tests have been carried out on two types of steel. Stress-states from uniaxial tension to equi-biaxial tension are covered. The quasi-static test describes well the sheet behaviour under low-velocity loading. The simulated force-displacement curves and strain histories agree with experiments. Most of the tests fail due to local necking. Abstract: Low-velocity impact tests were performed on dual-phase and martensitic steel sheets and compared with corresponding quasi-static tests. The geometry and loading condition of the specimens were similar to formability tests, and the average strain rates before failure were in the range 80–210 s − 1 for the low-velocity tests and 0.002-0.005 s − 1 for the quasi-static tests. For both loading rates, the sheets failed under pre-dominant membrane loading, and by varying the specimen geometry, the stress states prior to failure ranged from uniaxial tension to equi-biaxial tension. Thus, the most important stress states occurring during an impact event in a thin-walled structure are covered. The experiments were complemented by nonlinear finite element simulations, where higher-order solid elements and a refined mesh were applied to capture the failure of the sheets. The materials were modelled using the Hershey high-exponent yield function combined with the associated flow rule and isotropic hardening. Quasi-static tensile and shear tests and tensile tests at elevated strain rates were performed to calibrate the constitutive relation. The results in terms of force-displacement curves and strain histories at critical positions in the specimens were similar for low-velocity and quasi-static loading, independent of material and specimen geometry. This indicates that the quasi-static test gives a good description of the sheet behaviour under low-velocity impact loading. The numerical simulations were found to be in good agreement with the experimental results, and strengthened the experimental finding that all the sheet-impact tests, except the martensitic steel sheet in a state close to equi-biaxial tension, displayed local necking before final fracture.